Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-25T13:13:28+01:00
1.
a)
⅓ x < x - 2
⅓ x - x < - 2
-⅔ x < - 2 /*(-³/₂)
x > 3
x∈ (3; +∞)
b)
x (x+3) + 3 ≤ (x-2)² + 7x
x² + 3x + 3 ≤ x² - 4x + 4 + 7x
x² + 3x - x² + 4x - 7x ≤ 4 - 3
0 ≤ 1
Zbiorem rozwiązań nierówności jest zbiór R, czyli x∈ R

c) x√₂ + 2√₃ < 2x
x√₂ - 2x < - 2√₃
x(√₂ - 2) < - 2√₃ /:(√₂ - 2)
x > - 2√₃ /√₂ - 2
x > - 2√₃(√₂ + 2) /(√₂ - 2)(√₂ + 2)
x > - 2√₃(√₂ + 2) / 2 - 4
x > - 2√₃(√₂ + 2) / - 2
x > √₃(√₂ + 2)
x > √₆ + 2√₃
czyli x∈ (√₆ + 2√₃; + ∞)

d) (x+5)(6-x) ≥ 0
x + 5 = 0 i 6 - x = 0
x = - 5 i -x = -6 /*(-1)
x = - 5 i x = 6
(x+5)(6-x) = -x² + x + 30, czyli ramiona paraboli w dół
x∈ [-5; 6]

a)
(x-5)(x+6) = 0
x - 5 = 0 i x + 6 = 0
x = 5 i x = - 6
czyli x₁ = 5 i x₂ = 6

b)
x³-2x² = 0
x²(x - 2) = 0
x² = 0 i x - 2 = 0
x = 0 i x = 2
czyli x₁ = 0 i x₂ = 2

c)
x³-2x²+2 = x
x³ - x - 2x² + 2 = 0
x(x² - 1) - 2(x² - 1) = 0
(x - 2)(x² - 1) = 0
(x - 2)(x - 1)(x + 1) = 0
x - 2 = 0 i x - 1 = 0 i x + 1 = 0
x = 2 i x = 1 i x = - 1
czyli x₁ = 2 i x₂ = 1 i x₃ = - 1